Secondary Traumatic Stress in Italian Police Officers: The Role of Job Demands and Job Resources - Acquadro Maran, Daniela; Zito, Margherita; Colombo, Lara (Frontiers in Psychology, 2020)
Police officers are among the workers most exposed to acute or chronic stressful events, which compromises their psychosocial well-being and physical health. Exposure to traumatic events, human suffering, problematic situations and episodes of violence can cause psychological damage and lead to the development of secondary traumatic stress. The aim of this research is to explore the effect of job demands and job resources on secondary traumatic stress in police officers. To better understand this phenomenon and its consequences in this population, police officers were compared with health care professionals working as first responders. An ad hoc questionnaire was administered to 112 and 286 health care professionals. The findings showed that compared with health care workers, police officers suffer from secondary traumatic stress to a greater extent. Moreover, the results showed that some police officers suffered more than health care professionals regarding certain consequences of secondary traumatic stress, such as negative emotions and burnout. This study suggests implications and offers insights for both police officers and the organizations in which they work: police officer organizations should contribute to preventing the phenomenon of secondary traumatic stress by proposing programmes that implement resilience training and adaptive coping strategies.